The fundamentals of eye tracking part 6 : Working with areas of interest - Hooge, Ignace T C; Nyström, Marcus ; 0000-0002-2089-9012; Niehorster, Diederick C ; 0000-0002-4672-8756; Andersson, Richard; Foulsham, Tom; Nuthmann, Antje; Hessels, Roy S (Behavior Research Methods, 2026)
Researchers use area of interest (AOI) analyses to interpret eye-tracking data. This article addresses four key aspects of AOI use: 1) how to report AOIs to support replicable analyses, 2) how to interpret AOI-related statistics, 3) methods for generating both static and dynamic AOIs, and 4) recent developments and future directions in AOI use. The article underscores the importance of aligning AOI design with the study's conceptual and methodological foundations. It argues that critical decisions, such as the size, shape, and placement of AOIs, should be made early in the experimental design process and should involve eye-tracking data quality, the research question, participant tasks, and the nature of the visual stimulus. It also evaluates recent advances in AOI automation, outlining both their benefits and limitations. The article's main message is that researchers should plan AOIs carefully and explain their choices openly so others can replicate the work.
© 2026. The Author(s).
Keywords: Humans; Eye-Tracking Technology; Eye Movements/physiology; Research Design